Mitochondrial DNA and two Y‐chromosome genes of common long‐tailed macaques (Macaca fascicularis fascicularis) throughout Thailand and vicinity. Issue 2 (19th September 2016) - Bunlungsup, Srichan; Imai, Hiroo; Hamada, Yuzuru; Matsudaira, Kazunari; Malaivijitnond, Suchinda
Abstract : Macaca fascicularis fascicularis is distributed over a wide area of Southeast Asia. Thailand is located at the center of their distribution range and is the bridge connecting the two biogeographic regions of Indochina and Sunda. However, only a few genetic studies have explored the macaques in this region. To shed some light on the evolutionary history of M. f. fascicularis, including hybridization with M. mulatta, M. f. fascicularis and M. mulatta samples of known origins throughout Thailand and the vicinity were analyzed by molecular phylogenetics using mitochondrial DNA (mtDNA), including the hypervariable region 1, and Y‐chromosomal DNA, including SRY and TSPY genes. The mtDNA phylogenetic analysis divided M. f. fascicularis into five subclades (Insular Indonesia, Sundaic Thai Gulf, Vietnam, Sundaic Andaman sea coast, and Indochina) and revealed genetic differentiation between the two sides of the Thai peninsula, which had previously been reported as a single group of Malay peninsular macaques. From the estimated divergence time of the Sundaic Andaman sea coast subclade, it is proposed that after M. f. fascicularis dispersed throughout Southeast Asia, some populations on the south‐easternmost Indochina (eastern Thailand, southern Cambodia and southern Vietnam at the present time) migrated south‐westwards across the land bridge, which was exposed during the glacial period of the late Pleistocene epoch, to the southernmost Thailand/northern peninsular Malaysia. Then, some of them migrated north and south to colonize the Thai Andaman sea coast and northern Sumatra, respectively. The SRY‐TSPY phylogenetic analysis suggested that male‐mediated gene flow from M. mulatta southward to M. f. fascicularis was restricted south of, but close to, the Isthmus of Kra. There was a strong impact of the geographical factors in Thailand, such as the Isthmus of Kra, Nakhon Si Thammarat, and Phuket ranges and Sundaland, on M. f. fascicularis biogeography and their hybridization with M. mulatta .